Integration of Tradition and Technology: Digitalization Strategies in Islamic Education at Pesantren in Banyuwangi, Indonesia - Happyana, Lu'at; Istiqomah, Fina Zaidatul; Khasanah, Miratu; Hussin, Mohamad (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study analyzes the strategies employed by pesantren to manage cultural conflicts in non-Muslim communities. Using a qualitative approach with a case study method, data were collected through interviews, observations, and documentation, and subsequently analyzed using an interactive model, which included data reduction, data presentation, data depiction, and conclusion drawing. The results revealed that the pesantren implemented various strategies, such as intercultural dialogue, joint social activities, synergy in religious social events, collaboration with government agencies, and enhancing their image through achievements. These strategies play a crucial role in preventing and resolving cultural conflicts, as well as fostering harmonious relationships with the surrounding community. This research demonstrates that pesantren serve not only as religious education institutions but also as social agents that contribute to intercultural integration and harmony, particularly in plural societies. These findings underscore the significant role of pesantren in promoting cross-cultural dialogue and collaboration, ultimately fostering more inclusive and harmonious relationships in non-Muslim communities.